Celebrity Endorsement and Purchase Intention: A Study of the Role of Attractiveness, Trustworthiness, Expertise and Subjective Norm in Soft Drink Industry in Pakistan - Ali, Muhammad; Zahid Majeed; Ghina Saleem (Journal of Innovative Research in Management Sciences, 2024)
Purpose - This study seeks to help marketers in developing an effective marketing promotional strategy, particularly in the soft drink industry. Celebrity advertising has become a common practice in marketing, but the selection of appropriate celebrities is still a challenge. Among the factors that determine the extent to which celebrity endorsement would be effective, attributes of celebrity are of great importance which include physical attractiveness, trustworthiness, and expertise of the celebrity. Moreover, the effect of the attributes of celebrity on purchase intention may also be moderated by subjective norms of the consumers as suggested by the theory of planned behavior. Therefore, the present study intends to explore the role of a celebrity’s physical attractiveness, trustworthiness, and expertise on consumers’ purchase intention along with the moderating role of subjective norms for all three attributes among soft drink consumers in Pakistan. Study Design/methodology/approach - This study involved a survey method. Adapted questionnaires were used for data collection through convenience sampling from 392 participants. Multiple linear regression was used to evaluate the effect of a celebrity’s physical attractiveness, trustworthiness, and expertise on the purchase intention of the consumers. Findings - The results showed a significant relationship between celebrity physical attractiveness and purchase intention and between trustworthiness and purchase intention. A non-significant relationship between celebrity expertise and purchase intention was found. Research Practical Implications - The findings of this study can provide a basis for future research and business to understand and predict the behavior of soft drink consumers. It particularly suggests that marketers consider physical attractiveness and trustworthiness more seriously while recruiting celebrities for advertising. Originality/value - Since research on the impact of celebrity endorsement on purchase intention with the moderating role of the subjective norm in the soft drink industry of Pakistan is scarce, the present study is expected to make a new and insightful contribution to the field.